2017
DOI: 10.3390/polym9070276
|View full text |Cite
|
Sign up to set email alerts
|

Smart Poly(imidazoyl-l-lysine): Synthesis and Reversible Helix-to-Coil Transition at Neutral pH

Abstract: Polypeptide polymers can adopt natural protein secondary structures such as α-helices or β-sheets, and this unique feature is at the origin of some intriguing physico-chemical properties.In this work, we present how side chain imidazoylation of a poly(L-lysine) scaffold affords the preparation of poly(histidine) counterparts exhibiting α-helix conformation. This structuring behavior is reversible and can be controlled by means of pH and or temperature changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…These findings show the possibility for developing pH-sensitive collagen-based materials which can selectively release cargo molecules at low pH [26]. A similar concept was reported by imidazoylated poly- l -lysine (PLL) [27]. PLL is endowed with a random-coiled conformation because of dominant electrostatic repulsion.…”
Section: Ph-responsive Polypeptidesmentioning
confidence: 56%
See 4 more Smart Citations
“…These findings show the possibility for developing pH-sensitive collagen-based materials which can selectively release cargo molecules at low pH [26]. A similar concept was reported by imidazoylated poly- l -lysine (PLL) [27]. PLL is endowed with a random-coiled conformation because of dominant electrostatic repulsion.…”
Section: Ph-responsive Polypeptidesmentioning
confidence: 56%
“…PLL is endowed with a random-coiled conformation because of dominant electrostatic repulsion. To form a pH-sensitive helical structure, the imidazole moieties were attached to the primary amines of the PLL by the formation of amide bonds [27]. It was observed that imidazoylated PLL underwent a pH-triggered conformational transition from an alpha helix to a random coil structure with a decreasing pH level [27].…”
Section: Ph-responsive Polypeptidesmentioning
confidence: 99%
See 3 more Smart Citations